Moisture-absorbing quick-drying super-cool comfortable fabric and preparation method thereof
Through the blending technology of modified polyester fiber, cotton fiber and nylon fiber and the use of modified graphene powder, combined with the padding finishing and ultraviolet light irradiation process, the problems of poor cooling effect and degradation of mechanical properties of existing cool fabrics are solved, and the continuous cooling feeling and good mechanical properties of the fabric are achieved.
Patent Information
- Application Number
- CN202411797779.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The cool effect of existing cool fabrics is average, and the cool effect will be weakened after multiple cleanings. The cooling effect will be directly mixed into the fibers and will affect the structure and orientation of the fibers, resulting in a decrease in the mechanical properties of the fabric.
The blending technology of modified polyethylene terephthalate is adopted to modify the polyethylene terephthalate through modified graphene powder to improve the thermal and hygroscopic properties of the fibers, and enhance the coolness of the fabric through processes such as plunging and finishing and ultraviolet light irradiation.
The fabric is continuously provided with a cool feeling, and has good elasticity, moisture absorption and comfort, avoiding the influence of the fiber structure by cool substances and improving the mechanical properties of the fabric.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cool fabrics, and in particular to a moisture-absorbing quick-drying super cool and comfortable fabric and a preparation method thereof. Background Art
[0002] As people's quality of life improves, the demand for fabric functionality is also increasing. While pursuing beauty, people's demand for comfort is also increasing. Among them, cool fabrics can achieve a comfortable and cool wearing experience in hot environments by absorbing heat, accelerating perspiration and cooling, so they are favored by the market.
[0003] At present, the cooling effect of fabrics is usually achieved by post-finishing padding, which often has a general cooling effect and weakens after repeated washing. Therefore, a method of directly mixing cooling substances into fibers and then using cooling fibers to make fabrics has emerged. However, after these cooling substances are mixed into fibers, they will affect the original structure and orientation of the fibers, resulting in a decrease in the mechanical properties of the fabric. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a moisture-absorbing quick-drying super cool and refreshing fabric and a preparation method thereof.
[0005] The technical scheme of the present invention is: a moisture-absorbing quick-drying super cool and comfortable fabric, which is made by weaving 60-70 parts of modified polyester fiber, 20-30 parts of cotton fiber and 10-20 parts of nylon fiber by weight.
[0006] Note: The modified polyester fiber in the above-mentioned comfortable fabric has good thermal conductivity, strength and wear resistance, which can ensure that the comfortable fabric continues to provide a cool feeling. When mixed with cotton fiber and nylon fiber to make the fabric, the fabric has good elasticity, moisture absorption and comfort.
[0007] Furthermore, the preparation method of the modified polyester fiber is:
[0008] S1, dissolving polyethylene terephthalate in ethylene glycol, then adding modified graphene powder into the ethylene glycol, stirring for 5 to 15 minutes, to obtain a mixed solution; wherein the mixed solution comprises, by weight, 20 to 35 parts of polyethylene terephthalate, 1 to 5 parts of modified graphene powder, and 70 to 80 parts of ethylene glycol;
[0009] S2, adding a catalyst and a cross-linking agent to the mixed solution, then heating the mixed solution with a microwave heater to 70-90° C., keeping the temperature for 30-40 minutes, and continuing to heat to 180-200° C., keeping the temperature for 10-20 minutes, and continuously stirring during the heat preservation process, and obtaining a spinning solution after the heat preservation is completed; the amount of the catalyst added accounts for 2-4% of the mass of the mixed solution, and the amount of the cross-linking agent added accounts for 5-8% of the mass of the mixed solution;
[0010] S3. Spinning the spinning solution using a spinning machine to obtain modified polyester fibers.
[0011] Description: The above method modifies polyethylene terephthalate by modifying graphene powder, and the fatty acid loaded on the modified graphene powder can undergo esterification reaction with ethylene glycol under microwave heating to generate fatty acid ethylene glycol ester, and polyethylene terephthalate will undergo cross-linking reaction under microwave heating to form cross-linking bonds between fatty acid ethylene glycol ester and polyethylene terephthalate, thereby improving the compatibility between the modified graphene powder and polyethylene terephthalate, avoiding the influence of graphene powder on the strength of polyester fiber, and making the modified polyester fiber have good thermal conductivity and moisture absorption properties, and have higher strength and thermal stability.
[0012] Furthermore, in step S1, the method for preparing the modified graphene powder comprises the following steps:
[0013] S1-1, placing graphite powder in concentrated sulfuric acid, stirring at 0-5°C for 1-2h, and then filtering and washing in sequence to obtain graphite oxide; wherein the mass ratio of graphite powder to concentrated sulfuric acid is 1:20-30;
[0014] S1-2, placing graphite oxide in anhydrous ethanol, and ultrasonically dispersing for 10 to 20 minutes to obtain a graphene dispersion; wherein the mass ratio of graphite oxide to anhydrous ethanol is 1:30 to 50;
[0015] S1-3, adding 3-aminopropyltriethoxysilane to the graphene dispersion, then heating the graphite oxide dispersion to 60-70°C under stirring, keeping it warm for 2-3 hours, and adding fatty acid to the graphene dispersion once every 30-40 minutes during the insulation process; wherein the amount of 3-aminopropyltriethoxysilane added accounts for 2-4% of the mass of the graphene dispersion, and the single amount of fatty acid added accounts for 0.6-0.8% of the initial mass of the graphene dispersion;
[0016] S1-4. After the heat preservation is completed, the graphene dispersion is filtered to obtain modified graphene powder.
[0017] Description: The above method obtains a graphene dispersion by oxidizing graphite powder and then ultrasonically treating it, and the graphene oxide in the graphene dispersion can be loaded with amino groups under the action of 3-aminopropyltriethoxysilane, and then the fatty acid is loaded on the graphene for modification through the adsorption effect between the amino group and the fatty acid. The modified graphene powder can undergo an esterification reaction with ethylene glycol, thereby improving the compatibility between the modified graphene powder and polyethylene terephthalate.
[0018] Furthermore, in step S1-1, the average particle size of the graphite powder is 5 to 20 μm.
[0019] Note: Graphene prepared from graphite powder with the above particle size has excellent mechanical properties and better dispersibility, and can be fully dispersed in ethylene glycol.
[0020] Furthermore, in step S2, the catalyst is sulfuric acid or p-toluenesulfonic acid.
[0021] Description: The above catalyst can accelerate the reaction rate between fatty acid and ethylene glycol loaded on modified graphene powder.
[0022] Furthermore, in step S2, the cross-linking agent is any one of benzoyl peroxide and dicumyl peroxide, or a mixture of multiple thereof in any ratio.
[0023] Note: The above cross-linking agent can chemically react with ester groups, hydroxyl groups and the like to form cross-linking bonds between polyethylene terephthalate and fatty acid ethylene glycol ester, thereby improving the compatibility between the modified graphene powder and polyethylene terephthalate.
[0024] Furthermore, in step S3, the spinning temperature during the spinning is 250-280° C., and the spinning speed is 500-700 m / min.
[0025] Note: The above spinning parameters can ensure the fluidity of the spinning solution and the breaking strength and elongation of the fiber.
[0026] On the other hand, the preparation method of the above-mentioned comfortable fabric comprises the following steps:
[0027] Step 1: Immerse the fabric into the finishing agent for padding finishing, the bath ratio during immersion is 1:20-30, the temperature of the finishing agent is 60-70°C, and the immersion time is 10-30 minutes;
[0028] Step 2: After the impregnation is completed, the fabric is reciprocated by using a rolling mill. During the rolling process, ultraviolet light is used to irradiate the fabric on both sides of the roller. The width of the ultraviolet light is 2 to 4 cm, and the light intensity is 3 to 5 W / cm 2 During the reciprocating rolling process, the rolling rate of the fabric is n, and the moving speed of the fabric changes with the change of the rolling rate n, as follows:
[0029] 1) When n≥50%, the moving speed of the fabric is 4-5m / min;
[0030] 2) When 25<n<50%, the moving speed of the fabric is 2~3m / min;
[0031] 3) When the rolling rate during reciprocating rolling is ≤25%, the moving speed of the fabric is 3-4m / min;
[0032] When the rolling rate is less than or equal to 15%, the rolling is stopped to obtain a comfortable fabric.
[0033] Description: The preparation method is to prepare a fabric with good thermal conductivity by weaving a blend of modified polyester fiber, cotton fiber and nylon fiber, and then padding and finishing the fabric. When the water content inside the fabric is high, the fabric is quickly passed through the roller to reduce the water content of the fabric, so that the polycaprolactone can fully diffuse into the fabric with the finishing agent components, thereby increasing the finishing speed. After the water content inside the fabric decreases, the fabric movement speed is reduced so that the fabric can fully receive ultraviolet light irradiation, so that the polycaprolactone can absorb ultraviolet light and release the finishing agent components. As the water content of the fabric continues to decrease, the fabric movement speed begins to accelerate, avoiding excessive ultraviolet light per unit area on the fabric, resulting in damage to the fiber structure and a decrease in fabric strength. The finishing agent components are fully released into the fabric through padding and finishing, thereby further improving the thermal conductivity of the fabric and giving the fabric a cooling effect.
[0034] Furthermore, the finishing agent comprises, by weight: 30-40 parts of polycaprolactone, 4-8 parts of menthol, 5-10 parts of polydimethylsiloxane, 3-6 parts of xylitol, 1-5 parts of cetyltrimethylammonium chloride, 5-15 parts of anhydrous ethanol and 70-90 parts of deionized water.
[0035] Description: The above finishing agent has good finishing effect, can further enhance the moisture absorption and thermal conductivity of the fabric, enhance the cooling effect, and the cooling effect lasts for a long time.
[0036] The beneficial effects of the present invention are:
[0037] (1) The modified polyester fiber in the comfortable fabric of the present invention has good thermal conductivity, strength and wear resistance, ensuring that the comfortable fabric continuously provides a cool feeling, and is mixed with cotton fiber and nylon fiber to form a fabric, so that the fabric has good elasticity, moisture absorption and comfort.
[0038] (2) The present invention modifies polyethylene terephthalate by modifying graphene powder, thereby improving the compatibility between the modified graphene powder and polyethylene terephthalate, avoiding the influence of the graphene powder on the strength of the polyester fiber, and making the modified polyester fiber have good thermal conductivity and moisture absorption properties, as well as high strength and thermal stability. DETAILED DESCRIPTION
[0039] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0040] Embodiment 1: A moisture-absorbing quick-drying super cool and comfortable fabric, which is made by weaving a blend of 65 parts of modified polyester fiber, 25 parts of cotton fiber and 15 parts of nylon fiber by weight;
[0041] The preparation method of the modified polyester fiber is:
[0042] S1, dissolving polyethylene terephthalate in ethylene glycol, then adding modified graphene powder into the ethylene glycol, stirring for 10 minutes, to obtain a mixed solution; wherein the mixed solution comprises, by weight, 28 parts of polyethylene terephthalate, 2 parts of modified graphene powder and 75 parts of ethylene glycol;
[0043] S2, adding a catalyst and a cross-linking agent to the mixed solution, then heating the mixed solution with a microwave heater, heating to 80°C, keeping the temperature for 35 minutes, and continuing to heat to 190°C, keeping the temperature for 15 minutes, and continuously stirring during the heat preservation process, and obtaining a spinning solution after the heat preservation is completed; the amount of the catalyst added accounts for 3% of the mass of the mixed solution, and the amount of the cross-linking agent added accounts for 7% of the mass of the mixed solution; wherein the catalyst is p-toluenesulfonic acid, and the cross-linking agent is diisocyanate;
[0044] S3, using a spinning machine to spin the spinning solution to obtain modified polyester fiber; wherein the spinning temperature during spinning is 265° C. and the spinning speed is 600 m / min;
[0045] In step S1, the method for preparing the modified graphene powder comprises the following steps:
[0046] S1-1, placing graphite powder in concentrated sulfuric acid, stirring at 2°C for 1.5h, and then filtering and washing in sequence to obtain graphite oxide; wherein the mass ratio of graphite powder to concentrated sulfuric acid is 1:25, the mass concentration of concentrated sulfuric acid is 90%, and the average particle size of graphite powder is 5-20μm;
[0047] S1-2, placing graphite oxide in anhydrous ethanol and ultrasonically dispersing for 15 minutes to obtain a graphene dispersion; the mass ratio of graphite oxide to anhydrous ethanol is 1:40;
[0048] S1-3, adding 3-aminopropyltriethoxysilane to the graphene dispersion, then heating the graphite oxide dispersion to 65°C under stirring, keeping the temperature for 2.5 hours, and adding fatty acid to the graphene dispersion once every 35 minutes during the insulation process; wherein the amount of 3-aminopropyltriethoxysilane added accounts for 3% of the mass of the graphene dispersion, and the single amount of fatty acid added accounts for 0.7% of the initial mass of the graphene dispersion;
[0049] S1-4, after the heat preservation is completed, the graphene dispersion is filtered to obtain modified graphene powder;
[0050] The preparation method of the above-mentioned moisture-absorbing quick-drying super cool and comfortable fabric comprises the following steps:
[0051] Step 1: Immerse the fabric into the finishing agent for padding finishing. The bath ratio during immersion is 1:25, the temperature of the finishing agent is 65°C, and the immersion time is 20 minutes.
[0052] Step 2: After impregnation, the fabric is reciprocated by using a rolling mill. During rolling, ultraviolet light is used to irradiate the fabric on both sides of the roller. The width of the ultraviolet light is 3cm and the light intensity is 4W / cm 2 During the reciprocating rolling process, the rolling rate of the fabric is n, and the moving speed of the fabric changes with the change of the rolling rate n, as follows:
[0053] 1) When n≥50%, the fabric moving speed is 4.5m / min;
[0054] 2) When 25<n<50%, the moving speed of the fabric is 2.5m / min;
[0055] 3) When the rolling rate during reciprocating rolling is ≤25%, the moving speed of the fabric is 3.5m / min;
[0056] When the rolling rate is less than or equal to 15%, the rolling is stopped to obtain a comfortable fabric.
[0057] The finishing agent comprises, by weight: 35 parts of polycaprolactone, 6 parts of menthol, 8 parts of polydimethylsiloxane, 4 parts of xylitol, 3 parts of cetyltrimethylammonium chloride, 10 parts of anhydrous ethanol and 80 parts of deionized water.
[0058] Example 2: This example is basically the same as Example 1, except that the comfortable fabric is made by weaving a blend of 60 parts of modified polyester fiber, 20 parts of cotton fiber, and 10 parts of nylon fiber.
[0059] Example 3: This example is basically the same as Example 1, except that the comfortable fabric is woven from a blend of 70 parts of modified polyester fiber, 30 parts of cotton fiber, and 20 parts of nylon fiber.
[0060] Example 4: This example is basically the same as Example 1, except that the mixed solution comprises, by weight, 20 parts of polyethylene terephthalate, 1 part of modified graphene powder, and 70 parts of ethylene glycol.
[0061] Example 5: This example is basically the same as Example 1, except that the mixed solution comprises, by weight, 35 parts of polyethylene terephthalate, 5 parts of modified graphene powder and 80 parts of ethylene glycol.
[0062] Example 6: This example is basically the same as Example 1, except that the mixed solution is heated to 70°C and kept warm for 30 minutes, and then heated to 180°C and kept warm for 10 minutes.
[0063] Example 7: This example is basically the same as Example 1, except that the mixed solution is heated to 90°C with a microwave heater, kept warm for 40 minutes, and then continued to be heated to 200°C and kept warm for 20 minutes.
[0064] Example 8: This example is basically the same as Example 1, except that the amount of catalyst added accounts for 2% of the mass of the mixed solution.
[0065] Example 9: This example is basically the same as Example 1, except that the amount of catalyst added accounts for 4% of the mass of the mixed solution.
[0066] Example 10: This example is basically the same as Example 1, except that the amount of the cross-linking agent added is 5% of the mass of the mixed solution.
[0067] Example 11: This example is basically the same as Example 1, except that the amount of the cross-linking agent added accounts for 8% of the mass of the mixed solution.
[0068] Example 12: This example is basically the same as Example 1, except that the mass ratio of graphite powder to concentrated sulfuric acid is 1:20.
[0069] Example 13: This example is basically the same as Example 1, except that the mass ratio of graphite powder to concentrated sulfuric acid is 1:30.
[0070] Example 14: This example is basically the same as Example 1, except that the mass ratio of graphite oxide to anhydrous ethanol is 1:30.
[0071] Example 15: This example is basically the same as Example 1, except that the mass ratio of graphite oxide to anhydrous ethanol is 1:50.
[0072] Example 16: This example is basically the same as Example 1, except that the added amount of 3-aminopropyltriethoxysilane accounts for 2% of the mass of the graphene dispersion.
[0073] Example 17: This example is basically the same as Example 1, except that the added amount of 3-aminopropyltriethoxysilane accounts for 4% of the mass of the graphene dispersion.
[0074] Example 18: This example is basically the same as Example 1, except that the single addition amount of fatty acid accounts for 0.6% of the initial mass of the graphene dispersion.
[0075] Example 19: This example is basically the same as Example 1, except that the single addition amount of fatty acid accounts for 0.8% of the initial mass of the graphene dispersion.
[0076] Example 20: This example is basically the same as Example 1, except that the bath ratio during immersion is 1:20.
[0077] Example 21: This example is basically the same as Example 1, except that the bath ratio during immersion is 1:30
[0078] Example 22: This example is basically the same as Example 1, except that:
[0079] 1) When n≥50%, the fabric moving speed is 4m / min;
[0080] 2) When 25<n<50%, the fabric moving speed is 2m / min;
[0081] 3) When the rolling rate during reciprocating rolling is ≤25%, the moving speed of the fabric is 3m / min.
[0082] Embodiment 23: This embodiment is basically the same as Embodiment 1, except that:
[0083] 1) When n≥50%, the fabric moving speed is 5m / min;
[0084] 2) When 25<n<50%, the fabric moving speed is 3m / min;
[0085] 3) When the rolling rate during reciprocating rolling is ≤25%, the moving speed of the fabric is 4m / min.
[0086] Example 24: This example is basically the same as Example 1, except that the finishing agent comprises, by weight: 30 parts of polycaprolactone, 4 parts of menthol, 5 parts of polydimethylsiloxane, 3 parts of xylitol, 1 part of cetyltrimethylammonium chloride, 5 parts of anhydrous ethanol and 70 parts of deionized water.
[0087] Example 25: This example is basically the same as Example 1, except that the finishing agent comprises, by weight: 40 parts of polycaprolactone, 8 parts of menthol, 10 parts of polydimethylsiloxane, 6 parts of xylitol, 5 parts of cetyltrimethylammonium chloride, 15 parts of anhydrous ethanol and 90 parts of deionized water.
[0088] Comparative Example 1: Taking Example 1 as a reference, the modified polyester fiber was replaced with ordinary polyester fiber.
[0089] Comparative Example 2: Taking Example 1 as a reference, the modified graphene powder was replaced with ordinary graphene powder.
[0090] Comparative Example 3: With reference to Example 1, the mixed solution was heated directly to 190° C. and kept warm for 15 minutes.
[0091] Comparative Example 4: Using Example 1 as a reference, the fatty acids were added all at once.
[0092] Comparative Example 5: Using Example 1 as a reference, the fabric was not subjected to padding finishing.
[0093] Comparative Example 6: Taking Example 1 as a reference, the moving speed of the fabric during the reciprocating pressing process was constant at 2.5 m / min.
[0094] Experimental example: In order to explore the influence of the parameters of each embodiment on the performance of the comfortable fabric, the test breaking strength of the comfortable fabric of each embodiment was measured according to the standard GB / T3923.1-2013, and the coolness coefficient was tested according to the standard GB / T35263-2017. The specific exploration is as follows:
[0095] Experimental Example 1: Exploring the influence of ingredients on the performance of comfortable fabrics
[0096] Using Examples 1 to 3 and Comparative Example 1 as experimental comparison, the comfortable fabric performance under different ingredients is shown in Table 1 below:
[0097] Table 1 Comfortable fabric performance under different ingredients
[0098] Group Breaking strength / N Coolness coefficient Example 1 322 0.49 Example 2 302 0.45 Example 3 309 0.46 Comparative Example 1 330 0.29
[0099] It can be seen from the data in Table 1 that compared with Examples 1 to 3, the refreshing fabric of Example 1 has the highest breaking strength and cooling coefficient, indicating that the refreshing fabric of Example 1 has the highest strength and the best cooling effect, so the refreshing fabric component selected in Example 1 is the best;
[0100] Compared with Comparative Example 1, although the use of modified polyester fiber in Example 1 reduces the breaking strength, the reduction is small, and the coolness coefficient is significantly improved, which shows that the modification method of Example 1 can improve the coolness coefficient of polyester fiber and has little effect on the strength. Therefore, the comfortable fabric component selected in Example 1 is better.
[0101] Experimental Example 2: Investigating the influence of modified polyester fiber preparation parameters on the performance of comfortable fabrics
[0102] Using Example 1, Examples 4 to 11 and Comparative Examples 2 to 3 as experimental comparisons, the comfortable fabric properties of the modified polyester fiber under different preparation parameters are shown in Table 2 below:
[0103] Table 2 Comfortable fabric performance of modified polyester fiber under different preparation parameters
[0104] Group Breaking strength / N Coolness coefficient Example 1 322 0.49 Example 4 316 0.47 Example 5 303 0.43 Example 6 309 0.45 Example 7 302 0.42 Example 8 310 0.46 Example 9 313 0.43 Example 10 308 0.45 Embodiment 11 301 0.41 Comparative Example 2 288 0.32 Comparative Example 3 294 0.39
[0105] It can be seen from the data in Table 2 that compared with Examples 1, 4, and 5, the comfortable fabric of Example 1 has the highest breaking strength and coolness coefficient, indicating that the comfortable fabric of Example 1 has the highest strength and the best coolness effect. This may be because the modified graphene powder reacts most fully under the mixed solution ratio of Example 1 and has the best compatibility with polyethylene terephthalate, so the mixed solution ratio selected in Example 1 is optimal;
[0106] Compared with Examples 1, 6, and 7, the comfortable fabric of Example 1 has the highest breaking strength and coolness coefficient, indicating that the comfortable fabric of Example 1 has the highest strength and the best coolness effect. This may be because the fatty acid esterification rate on the modified graphene powder is higher under the heating parameters of Example 1, and more cross-linking bonds are formed between fatty acid ethylene glycol ester and polyethylene terephthalate;
[0107] Compared with Examples 1, 8 to 11, too high or too low addition amounts of the catalyst and the cross-linking agent will lead to a decrease in the breaking strength and the coolness coefficient, while the breaking strength and the coolness coefficient of the comfortable fabric of Example 1 are the highest. This may be because under the addition amounts of the catalyst and the cross-linking agent of Example 1, the modified graphene powder and polyethylene terephthalate have the best compatibility, so the addition amounts of the catalyst and the cross-linking agent selected in Example 1 are optimal;
[0108] Compared with Comparative Example 2, after the modified graphene powder is replaced by ordinary graphene powder, the breaking strength of the comfortable fabric is reduced and the coolness coefficient is significantly reduced. This may be because the compatibility of ordinary graphene powder with polyethylene terephthalate is poor, and ordinary graphene powder cannot be evenly distributed in the polyester fiber. Therefore, the modified graphene powder used in Example 1 is better;
[0109] Compared with comparative example 3, after directly heating to 190°C, the breaking strength and the coolness coefficient of the comfortable fabric in Example 1 decreased. This may be because the fatty acid on the modified graphene powder cannot be fully esterified due to direct heating to 190°C. Therefore, the heating parameters selected in Example 1 are better.
[0110] Experimental Example 3: Investigating the influence of modified graphene powder preparation parameters on the performance of comfortable fabrics
[0111] Using Example 1, Examples 12 to 19 and Comparative Example 4 as experimental comparisons, the comfortable fabric performance of the modified graphene powder under different preparation parameters is shown in Table 3 below:
[0112] Table 3 Comfortable fabric performance under different preparation parameters of modified graphene powder
[0113] Group Breaking strength / N Coolness coefficient Example 1 322 0.49 Example 12 310 0.44 Example 13 301 0.42 Embodiment 14 315 0.46 Embodiment 15 312 0.45 Example 16 314 0.47 Embodiment 17 325 0.49 Embodiment 18 306 0.43 Embodiment 19 323 0.49 Comparative Example 4 298 0.40
[0114] It can be seen from the data in Table 3 that compared with Examples 1, 12, and 13, the comfortable fabric of Example 1 has the highest breaking strength and coolness coefficient, indicating that the comfortable fabric of Example 1 has the highest strength and the best coolness effect. This may be because under the mass ratio of graphite powder to concentrated sulfuric acid in Example 1, the graphite powder is oxidized while the structure remains intact, so the mass ratio of graphite powder to concentrated sulfuric acid selected in Example 1 is optimal;
[0115] Compared with Examples 1, 14, and 15, the comfortable fabric of Example 1 has the highest breaking strength and coolness coefficient, indicating that the comfortable fabric of Example 1 has the highest strength and the best coolness effect. This may be because the graphite oxide is more evenly dispersed and the conversion rate to graphene is higher under the mass ratio of graphite oxide to anhydrous ethanol in Example 1.
[0116] Compared with Examples 1 and 16 to 19, as the amount of 3-aminopropyltriethoxysilane and fatty acid added increases, the breaking strength and cool coefficient of the comfortable fabric gradually increase until the breaking strength and cool coefficient of the comfortable fabric of Example 1 reach the highest. As the amount of 3-aminopropyltriethoxysilane and fatty acid added continues to increase, the breaking strength and cool coefficient of the comfortable fabric begin to have no obvious changes. This may be because the number of amino groups that can be loaded on graphene is limited. Therefore, from a cost perspective, the amount of 3-aminopropyltriethoxysilane and fatty acid added selected in Example 1 is optimal.
[0117] Compared with Comparative Example 4, in Example 1, after the fatty acids are added all at once, the breaking strength and coolness coefficient of the comfortable fabric are reduced. This may be because after the fatty acids are added all at once, the fatty acids cannot be evenly loaded on the graphene. Therefore, the fatty acid addition method selected in Example 1 is the best.
[0118] Experimental Example 4: Investigating the influence of padding finishing parameters on the performance of comfortable fabrics
[0119] Using Example 1, Examples 20 to 23 and Comparative Example 5 as experimental comparisons, the comfortable fabric performance under different padding finishing parameters is shown in Table 4 below:
[0120] Table 4 Performance of comfortable fabrics under different padding finishing parameters
[0121] Group Breaking strength / N Coolness coefficient Example 1 322 0.49 Embodiment 20 308 0.43 Embodiment 21 316 0.47 Embodiment 22 313 0.46 Embodiment 23 315 0.45 Embodiment 24 314 0.45 Embodiment 25 311 0.44 Comparative Example 5 320 0.38 Comparative Example 6 318 0.41
[0122] It can be seen from the data in Table 4 that compared with Examples 1, 20, and 21, the comfortable fabric of Example 1 has the highest breaking strength and coolness coefficient, indicating that the comfortable fabric of Example 1 has the highest strength and the best coolness effect. This may be because the fiber has the best absorption effect on the finishing agent under the bath ratio of Example 1, so the bath ratio selected in Example 1 is the best;
[0123] Compared with Examples 1, 22, and 23, the comfortable fabric of Example 1 has the highest breaking strength and coolness coefficient, indicating that the comfortable fabric of Example 1 has the highest strength and the best coolness effect. This may be because at the moving speed of the fabric of Example 1, the finishing agent components in the fabric are most evenly distributed and the finishing effect is the best. Therefore, the fabric moving speed selected in Example 1 is the best.
[0124] Compared with Examples 1, 24, and 25, the comfortable fabric of Example 1 has the highest breaking strength and coolness coefficient, indicating that the comfortable fabric of Example 1 has the highest strength and the best coolness effect. This may be because the fiber has the best absorption effect on the finishing agent of Example 1, so the finishing agent component selected in Example 1 is the best;
[0125] Compared with Example 5, when the fabric is not subjected to padding finishing, the coolness coefficient of the comfortable fabric still decreases in Example 1, which indicates that padding finishing can further improve the coolness coefficient of the comfortable fabric.
[0126] Compared with comparative example 6, in Example 1, after the moving speed of the fabric was constant during the reciprocating pressing process, the coolness coefficient of the refreshing fabric still decreased, which indicates that the pressing method selected in Example 1 has a better finishing effect.
Claims
1. A moisture-absorbing, quick-drying, ultra-cool and comfortable fabric, characterized in that: The comfortable fabric is made by weaving a blend of 60-70 parts of modified polyester fiber, 20-30 parts of cotton fiber and 10-20 parts of nylon fiber by weight.
2. The moisture-absorbing quick-drying super cool and refreshing fabric according to claim 1, characterized in that: The preparation method of the modified polyester fiber is: S1, dissolving polyethylene terephthalate in ethylene glycol, then adding modified graphene powder into the ethylene glycol, stirring for 5 to 15 minutes, to obtain a mixed solution; wherein the mixed solution comprises, by weight: 20 to 35 parts of polyethylene terephthalate, 1 to 5 parts of modified graphene powder and 70 to 80 parts of ethylene glycol; S2, adding a catalyst and a cross-linking agent to the mixed solution, then heating the mixed solution with a microwave heater to 70-90° C., keeping the temperature for 30-40 minutes, and continuing to heat to 180-200° C., keeping the temperature for 10-20 minutes, and continuously stirring during the heat preservation process, and obtaining a spinning solution after the heat preservation is completed; the amount of the catalyst added accounts for 2-4% of the mass of the mixed solution, and the amount of the cross-linking agent added accounts for 5-8% of the mass of the mixed solution; S3. Spinning the spinning solution using a spinning machine to obtain modified polyester fibers.
3. The moisture-absorbing quick-drying super cool and comfortable fabric according to claim 2, characterized in that: In step S1, the method for preparing the modified graphene powder comprises the following steps: S1-1, placing graphite powder in concentrated sulfuric acid, stirring at 0-5°C for 1-2h, and then filtering and washing in sequence to obtain graphite oxide; wherein the mass ratio of graphite powder to concentrated sulfuric acid is 1:20-30; S1-2, placing graphite oxide in anhydrous ethanol, and ultrasonically dispersing for 10 to 20 minutes to obtain a graphene dispersion; wherein the mass ratio of graphite oxide to anhydrous ethanol is 1:30 to 50; S1-3, adding 3-aminopropyltriethoxysilane to the graphene dispersion, then heating the graphite oxide dispersion to 60-70°C under stirring, keeping it warm for 2-3 hours, and adding fatty acid to the graphene dispersion once every 30-40 minutes during the insulation process; wherein the amount of 3-aminopropyltriethoxysilane added accounts for 2-4% of the mass of the graphene dispersion, and the single amount of fatty acid added accounts for 0.6-0.8% of the initial mass of the graphene dispersion; S1-4. After the heat preservation is completed, the graphene dispersion is filtered to obtain modified graphene powder.
4. The moisture-absorbing quick-drying super cool and comfortable fabric according to claim 3, characterized in that: In step S1-1, the average particle size of the graphite powder is 5 to 20 μm.
5. The moisture-absorbing quick-drying super cool and comfortable fabric according to claim 2, characterized in that: In step S2, the catalyst is sulfuric acid or p-toluenesulfonic acid.
6. The moisture-absorbing quick-drying super cool and comfortable fabric according to claim 2, characterized in that: In step S2, the cross-linking agent is any one of diisocyanate and triisocyanate, or a mixture of multiple types in any ratio.
7. The moisture-absorbing quick-drying super cool and comfortable fabric according to claim 2, characterized in that: In step S3, the spinning temperature during spinning is 250-280° C., and the spinning speed is 500-700 m / min.
8. A method for preparing a moisture-absorbing quick-drying super cool and refreshing fabric, used for preparing the moisture-absorbing quick-drying super cool and refreshing fabric as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: Immerse the fabric into the finishing agent for padding finishing, the bath ratio during immersion is 1:20-30, the temperature of the finishing agent is 60-70°C, and the immersion time is 10-30 minutes; Step 2: After the impregnation is completed, the fabric is reciprocated by using a rolling mill. During the rolling process, ultraviolet light is used to irradiate the fabric on both sides of the roller. The width of the ultraviolet light is 2 to 4 cm, and the light intensity is 3 to 5 W / cm 2 During the reciprocating rolling process, the rolling rate of the fabric is n, and the moving speed of the fabric changes with the change of the rolling rate n, as follows: 1) When n≥50%, the moving speed of the fabric is 4-5m / min; 2) When 25<n<50%, the moving speed of the fabric is 2~3m / min; 3) When the rolling rate during reciprocating rolling is ≤25%, the moving speed of the fabric is 3-4m / min; When the rolling rate is less than or equal to 15%, the rolling is stopped to obtain a comfortable fabric.
9. The method for preparing the moisture-absorbing quick-drying super cool and refreshing fabric according to claim 8, characterized in that: The finishing agent comprises, by weight: 30-40 parts of polycaprolactone, 4-8 parts of menthol, 5-10 parts of polydimethylsiloxane, 3-6 parts of xylitol, 1-5 parts of hexadecyltrimethylammonium chloride, 5-15 parts of anhydrous ethanol and 70-90 parts of deionized water.
Citation Information
Patent Citations
Preparation method of antibacterial fabric based on ultraviolet curing technology
CN108468209A
Graphene modified fiber blended yarn, fabric and production technology of graphene modified fiber blended yarn
CN108677307A
Production method of moisture-absorption cool fabric fibers
CN110359126A
Modified graphene fiber as well as preparation method and application thereof
CN115627557A
Preparation method of polyester silk-like woman dress printed cloth
CN116695471A